The nature of bioartifacts. Intentionalism, reproductivism, and nature - Parente, Diego (Revista de Filosofía, 2014)
This paper discusses some aspects of the ontological problem of bioartifacts in order to develop, within the vocabulary of philosophy of technical artifacts, a deflationed notion of bioartifact capable of revealing a meaningful distinction between those processes arisen from a natural dynamics not intentionally intervened, and those arisen from intentional intervention. With this purpose two ways of interpreting the nature of these entities (intentionalism and reproductivism) are reconstructed and evaluated. Finally this paper collects the previous arguments and tries to make explicit the levels of intentional intervention and the conditions to be a bioartifact.